A hybrid life cycle assessment of the large-scale application of electric vehicles. (1st February 2021) - Xiong, Siqin; Wang, Yunshi; Bai, Bo; Ma, Xiaoming
Abstract: China is actively supporting the electrification of passenger vehicles as it attempts to reduce carbon dioxide (CO2 ) emissions from the transportation sector. Through a hybrid life cycle assessment, this study aims to evaluate the CO2 emission reduction potential from this large-scale vehicle electrification. A comprehensive database of passenger electric vehicles sold in 2018 is established and future scenario analysis considering multiple technology advancements is integrated. The results indicate that this vehicle electrification fails to achieve emission savings in 2018, as extra emissions from manufacturing newly sold passenger electric vehicles exceed the avoided emissions from on-road vehicles. In 2030, the emission reductions could feasibly increase to 49.64 million tons and achieve up to 62.16 million tons in the optimistic scenario. By correlation analysis using market-based data in 2018 and scenario analysis in 2030, the fuel economy is identified as a crucial factor to deliver emission mitigation. Highlights: The vehicle electrification in China fails to save CO2 emissions in 2018. Potential CO2 emission reductions rises up to 60 million tons in 2030. Relationships among emissions, vehicle performance and sales are analysed. Fuel economy is a crucial factor to maximize the emission reduction potential. Plug-in hybrid electric vehicles gain prominent emission reductions by 2030.